2017
DOI: 10.1136/bcr-2017-219661
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cancer presenting as Lemierre’s syndrome caused byStreptococcus anginosus

Abstract: A 59-year-old man presented to the emergency department with complaints of dysphagia, right-sided neck swelling, fever and chills. Physical examination was remarkable for fever and tender swelling over the right side of the neck. Laboratory investigations revealed leucocytosis with neutrophilia. CT of the neck showed right internal jugular vein thrombosis with an overlying abscess and a nodular opacity in the right lung apex with air locules. He underwent surgical drainage of the neck abscess. Aerobic cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Since the initial symptom was intense dysphagia, the evacuation of the abscess was performed at first. Subsequently, upper digestive endoscopy was performed and esophageal cancer was discovered [56]. Other authors present the first case of proximal esophageal adenocarcinoma located in the thyroid in a young patient without any history of neoplasms [57].…”
mentioning
confidence: 99%
“…Since the initial symptom was intense dysphagia, the evacuation of the abscess was performed at first. Subsequently, upper digestive endoscopy was performed and esophageal cancer was discovered [56]. Other authors present the first case of proximal esophageal adenocarcinoma located in the thyroid in a young patient without any history of neoplasms [57].…”
mentioning
confidence: 99%
“…We found that 9 out of 16 patients did see a healthcare provider (56%) with one of them having been previously hospitalized before being transferred to another facility. and 9 of those 10 patients received antibiotics (56%) [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Whether these are truly causative agents, or F. necrophorum undetected, remains unknown. 13,14 Importantly, differences in the definition of the diagnostic criteria of Lemierre syndrome do not ultimately translate to different diagnostic and therapeutic approaches.…”
Section: Casementioning
confidence: 99%